Fatherhood research in Australia: Research report - Pascoe, S; Fairbairn, H; Fletcher, R (My University, 2004)
The Engaging Fathers project at the University of Newcastle initiated the Fatherhood Research in Australia Report to make available a description of recent research on fathers in Australian populations. The aim of the project was to: a) Describe the knowledge base available to support policies, programs and practices addressing fathers' contribution to families; b) Initiate links between researchers from dfferent disciplines who are examining aspects of fatherhood; c) Encourage future research on families to include fathers as a core componenet; and d) Identify research to support early intervention with fathers. The report explains the study methodology and presents information on the demography of Australian fathers. It then discusses the findings in the following sections: family formation; fathers and child development; fathers and family separation; work and family balance; fathers of young adults; illness; fathers with an illness or substance abuse; culturally and linguistically diverse fathers; and gay fathers. It looks at information about fathers in the Household, Income and Labour Dynamics in Australia (HILDA) survey, the Longitudinal Study of Australian Children (LSAC), and the Negotiating the Life Course Survey, and at research on program and service development and effectiveness.
Keywords: Families -- Fathers; Families; Families and relationships; Families; Fathers; Families and relationships